Decomposition of some pointed Hopf algebras given by the canonical Nakayama automorphism - Graña, M. (2007)
Every finite dimensional Hopf algebra is a Frobenius algebra, with Frobenius homomorphism given by an integral. The Nakayama automorphism determined by it yields a decomposition with degrees in a cyclic group. For a family of pointed Hopf algebras, we determine necessary and sufficient conditions for this decomposition to be strongly graded. © 2006 Elsevier Ltd. All rights reserved.